2004
DOI: 10.1023/b:mcbi.0000044389.65590.57
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling of the vascular tunica media is essential for development of collateral vessels in the canine heart

Abstract: Previous studies have shown that neointima formation and adventitial remodeling play an important role in the enlargement of collateral vessels (CVs) during coronary arteriogenesis in the dog heart. In this study, we investigated the importance of remodeling of the tunica media in the same model. Basal membrane (BM), contractile and cytoskeletal components of smooth muscle cells (SMCs) were studied in growth of coronary CVs induced by chronic occlusion of the left circumflex (LCX) coronary artery by routine hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
37
0
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 30 publications
8
37
0
5
Order By: Relevance
“…Earlier, TIMP-1 has been reported to be transcriptionally upregulated in a model for coronary arteriogenesis in the dog heart (Cai et al, 2004). In our study, mRNA ISH analysis showed TIMP-1-positive mRNA staining in the intima, media, and adventitia of the PCA during arteriogenesis 24 h after 3-VO ( Figure 3A).…”
Section: Discussionsupporting
confidence: 73%
“…Earlier, TIMP-1 has been reported to be transcriptionally upregulated in a model for coronary arteriogenesis in the dog heart (Cai et al, 2004). In our study, mRNA ISH analysis showed TIMP-1-positive mRNA staining in the intima, media, and adventitia of the PCA during arteriogenesis 24 h after 3-VO ( Figure 3A).…”
Section: Discussionsupporting
confidence: 73%
“…It comprises the induction of vascular wall cell proliferation and migration and includes wall remodelling processes. In consequence, the structural enlargement of collateral arterioles to arteries proceeds as an active growth rather than by a passive dilatation caused by the altered blood pressure [7][8][9] The initial trigger defines the mechanism Angiogenesis and arteriogenesis are initiated by distinct initial triggers. Especially during tissue expansion such as in growing tumors but also in ischemic tissues, adaptive growth of capillaries is initiated as a reaction to hypoxia [10][11][12].…”
mentioning
confidence: 99%
“…In the phase of active growth the cells of both the tunica media and adventitia are activated, indicated by reexpression of fetal proteins in smooth muscle cells (SMCs), active extracellular proteolysis, proliferation and migration of SMCs and fibroblasts, and neointima formation [Wolf et al, 1998;Cai et al, 2000Cai et al, , 2001Cai et al, , 2003]. In the maturation phase the collateral vessels stop growing and the SMCs of the neointima are present in the contractile phenotype with high levels of both the cytoskeletal and contractile proteins, for example desmin, α-SM actin and calponin [Cai et al, 2000[Cai et al, , 2004b. The outcome of vascular remodeling leads to larger arterial vessels that conduct blood to the ischemic regions.…”
Section: The Formation Of Aberrant Collateral Vessels During Coronarymentioning
confidence: 99%